Local Authorities In Klang Valley - A Study On The Effectiveness Of Service Delivery To Improve Public Satisfaction - Mohd Nawi, Ahmad Naji (2009)
The purpose of this project is to identify internal and external challenges which affect the local authorities' delivery system as well as developing a framework to identify factors that can influence the efficiency and effectiveness of local government delivery system.